Evaluation of enhanced darkfield microscopy and hyperspectral imaging for rapid screening of TiO2 and SiO2 nanoscale particles captured on filter media. Issue 12 (14th July 2021) - Neu‐Baker, Nicole M.; Dozier, Alan K.; Eastlake, Adrienne C.; Brenner, Sara A.
Abstract: Here we report on initial efforts to evaluate enhanced darkfield microscopy (EDFM) and light scattering Vis–NIR hyperspectral imaging (HSI) as a rapid screening tool for the offline analysis of mixed cellulose ester (MCE) filter media used to collect airborne nanoparticulate from work environments. For this study, the materials of interest were nanoscale titanium dioxide (TiO2 ) and silicon dioxide (SiO2 ; silica), chosen for their frequent use in consumer products. TiO2 and SiO2 nanoscale particles (NPs) were collected on MCE filter media and were imaged and analyzed via EDFM‐HSI. When visualized by EDFM, TiO2 and SiO2 NPs were readily apparent as bright spherical structures against a dark background. Moreover, TiO2 and SiO2 NPs were identified in hyperspectral images. EDFM‐HSI images and data were compared to scanning transmission electron microscopy (STEM), a NIST‐traceable technique for particle size analysis, and the current gold standard for offline analysis of filter media. As expected, STEM provided more accurate sizing and morphology data when compared to EDFM‐HSI, but is not ideal for rapid screening of the presence of NPs of interest since it is a costly, low‐throughput technique. In this study, we demonstrate the utility of EDFM‐HSI in rapidly visualizing and identifying TiO2 and SiO2 NPs on MCE filters. This screening method may prove useful in expediting time‐to‐knowledge compared to electron microscopy. Future work will expand this evaluation to other industrially relevant NPs, other filter media types, and real‐world filter samples from occupational exposure assessments. Abstract : Classified hyperspectral image of TiO2 NPs collected on MCE filter media. Hyperspectral datacube of TiO2 captured on MCE filter media (exposure concentration: 32.8 mg TiO2 ). Green false coloration overlay indicates TiO2 (+) pixels as identified by SAM. Scale bar = 50 μm. Enhanced darkfield microscopy‐hyperspectral imaging visualizes nanoparticles and identifies samples for further intensive electron microscopy analysis. This technique is promising for rapid screening of filters from occupational exposure assessments.